A Comprehensive Review On Prevalence And Risk Factors Of Eating Disorders And Unhealthy Eating Behaviors In Adolescents From Some States Of India Between 2010-2022 (International Journal of Food and Nutritional Sciences, 2022)
Purpose: Eating disorder (ED) is a psychological and lifestyle disorder characterized by obsessions with food, body weight, size and shape. Eating disorder involves unhealthy or disturbed behaviors and attitudes towards regular meal pattern. Adolescent girls are more prone to develop eating disorder than males and it negatively affects their physical and socio-economic health. Industrialization has now cultivated this western concept on Indian adolescent girls. Dieting practices sometimes lead to hospitalization and severe nutritional deficiencies. The objective of the review is to see the occurrence and prevalence of ED and identify the risk factors in various Indian states in last ten years.Methods: All the papers from 2000-2020 were reviewed from Google scholar and PubMed. Indian prevalence from 2010-2020 was collected from these databases and references of other studies. 12 Indian studies were included after literature study.Results: Fair percentage of ED was found to be prevalent in India. In India, fasting is normally accepted from religious belief and frequently festivals are celebrated with sweets and high calorie foods. So actual cause of disordered eating pattern including both anorexia and bulimia nervosa is very challenging to determine. Conclusion: The identification of ED cases is difficult even at advanced stage and sometimes become very fatal. Basic health and nutritional knowledge from early age, regular health check-up, good family relationship are important factors to prevent ED. An overall diagnostic tool and skilled health care personnel are required to detect the problem.